Effect of Lidocaine Clonidin on Tourniquet Pain at Regional Intravenous Anaesthesia - Yaşar, M. Akif; Dinçer, İdris; K.bayar, Mustafa; Keleşyılmaz, Nedim (Fırat University, 2002)
Aim: Intravenous regional anesthesia (RIVA) is a simple and common procedure to provide anesthesia and muscle relaxion for hand surgery. The problem occurs during RIVA is pain because of the tourniquet . This pain may prevented with double – tourniquet system RIVA. We investigated effect of clonidine added to RIVA local anesthetics and ring anestesia performed to tourniquet area for tourniquet pain. Material and methods: Thirty-six patients scheduled for elective hand surgery, ASAI-II groups aged between 20 and 50 were assigned randomly and blindly to three groups. Patients didn't receive premedication. The first group were received 40 ml 0,5% lidokain, ring anesthesia was performed with 40 ml 0.5% lidocain and 10 ml 1% lidocain in the second group. The third group were received 40 ml 0.5% lidocain and 150µg clonidine. Results: There was no significant differences between two groups according to tourniquet pain and pain in the surgery plains before and after tourniguet deflation (p>0.05). Motor block was not seen in any patient. Significant difference was not observed between two groups among the Ramsay's sedation scor. Conclusion: Adequate analgesia was provided for all patients. There was no difference according to the tolerance for tourniquet pain between ring anesthesia and addition of clonidine to RIVA solution.

Amaç: Rejyonel intravenöz anestezi (RİVA), üst ekstrimite cerrahisinde yeterli anestezi ve kas gevşemesi sağlayan basit fakat yaygın bir yöntemdir. RİVA'da ortaya çıkan önemli bir sorun turnike ağrısıdır. Bu ağrı klasik olarak çift turnike yöntemi ile önlenebilir. Çalışmamızın amacı RİVA'da lokal anesteziye ilave edilen klonidin ile turnike bölgesine uygulanan ring anestezisinin turnike ağrısına etkisini araştırmaktır. Gereç ve Yöntem: Yaşları 20-50 arası olan ASAI-II grubundan, elektif el cerrahisi planlanan 36 hasta çalışmaya dahil edildi. Premedikasyon verilmeyen hastalar rasgele üç gruba ayrıldı. RİVA uygulanacak hastalardan Grup I'e 40 ml %5 lidokain, Grup II'ye 40 ml %0.5 lidokain ve 10 ml %1'lik lidokain ile ring anestezisi, Grup III'ye 40 ml %0.5 lidokain ve 150 μg klonidin uygulanmıştır. Bulgular: Turnike ağrısı, cerrahi bölgede ağrı ve turnike gevşetildikten sonra cerrahi bölgede ağrı açısından her iki grup arasında anlamlı fark bulunamadı (p>0.05). Hiçbir hastada motor blok gelişmedi. Ramsay sedasyon skoru açısından anlamlı fark gözlenmedi (p>0.05). Tüm hastalarda yeterli analjezi sağlandı. Sonuç: RİVA'da lokal anestezik solüsyonuna eklenen 150 µg klonidin ile ring anestezisinin turnike ağrısına tolerans bakımından fark yoktur.
REJYONEL İNTRAVENÖZ ANESTEZİDE TURNİKE AĞRISINA LİDOKAİN-KLONİDİNİN ETKİSİ